Intraoperative apical ventricular septal defect closure using a modified Rashkind double umbrella. Issue 4 (October 1996) - Chaturvedi, R. R.; Shore, D. F.; Yacoub, M.; Redington, A. N.
Abstract : OBJECTIVE: To demonstrate the safety and efficacy of intraoperative apical ventricular septal defect (VSD) closure using a modified Rashkind double umbrella. DESIGN: Descriptive study of all patients in whom intraoperative device closure of apical VSDs was attempted. SETTING: A tertiary referral centre. PATIENTS: Four patients with an apical VSD requiring closure, during the period January 1993 to May 1995. INTERVENTIONS: Intraoperative placement of a modified Rashkind umbrella. RESULTS: Four successful placements resulting in apical VSD closure, as judged by transoesophageal colour flow mapping. Three patients received a 17 mm and one a 12 mm umbrella. Early complete closure was achieved in three patients. There was a small residual leak around the 12 mm device that had resolved at 5 month follow up. There was one early death, which was unrelated to VSD closure. CONCLUSION: Apical ventricular septal defects can be closed safely and effectively with intraoperative use of a modified Rashkind umbrella.